Profit-Sharing - Moreau, Ernest (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1951)
SummaryThis brief report of the last Congress of the Boards of Trade of the Province of Quebec brings new suggestions for the study and application of this idea under way: profit-sharing.